Reduced immunogenicity of BNT162b2 booster vaccination in combination with a tetravalent influenza vaccination: results of a prospective cohort study in 838 health workers. (May 2023) - Radner, Helga; Sieghart, Daniela; Jorda, Anselm; Fedrizzi, Clemens; Hasenöhrl, Timothy; Zdravkovic, Andrej; Redlberger-Fritz, Monika; Puchammer-Stoeckl, Elisabeth; Anderle, Karolina; Bergmann, Felix; Firbas, Christa; Jordakieva, Galateja; et al.
Abstract: Objective: To investigate the immunogenicity and safety of BNT162b2 booster vaccination with and without a tetravalent influenza vaccine. Methods: A prospective, open-label cohort study on immunogenicity and safety of COVID-19 booster vaccination with or without a tetravalent influenza vaccine was performed. Eight hundred thirty-eight health care workers were included in the following study arms: BNT162b2 booster-only, influenza-vaccine-only or combination of both. Levels of antibodies against SARS-CoV-2 spike receptor binding domain, and haemagglutinin inhibition tested for four different influenza strains (A(H1N1)pdm09, A(H3N2), B/Victoria, B/Yamagata) were measured at the time of vaccination and 4 weeks later. Results: After 4 weeks, median (interquartile range) levels of antibodies against the receptor binding domain of the viral spike (S) protein and relative change from baseline were high in individuals who received BNTb162b2 booster vaccination only (absolute: 16 600 [10 980–24 360] vs. 12 630 [8198–18 750] BAU/mL [p < 0.0001]; relative increase: 49% [23.6–95.3] vs. 40% [21.9–80.6] [p 0.048]; booster-only n  = 521 vs. combination-arm n  = 229 respectively). Results were confirmed after matching for sex, age, body mass index, baseline antibody levels and vaccine compound received for primary immunization (absolute: 13 930 [10 610–22 760] vs. 12 520 [8710–17 940]; [p 0.031]; relative increase: 55.7% [27.8–98.5] vs. 42.2% [22.9–74.5]; p 0.045). Adverse events were almost identical in the booster-only and the combination-arm, but numerically low in the influenza arm (525/536 [97.9%] vs. 235/240 [97.9%] vs. 26/33 [78.8 %]). Discussion: Although no safety concerns occurred, our study provides evidence on reduced immunogenicity of a BNT162b2 booster vaccination in combination with a tetravalent influenza vaccine. Further studies investigating new influenza variants as well as potential differences vaccine effectiveness are needed.